2010
DOI: 10.1007/s10461-010-9679-y
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Delivered in Clinical Settings are Effective in Reducing Risk of HIV Transmission Among People Living with HIV: Results from the Health Resources and Services Administration (HRSA)’s Special Projects of National Significance Initiative

Abstract: To support expanded prevention services for people living with HIV, the US Health Resources and Services Administration (HRSA) sponsored a 5-year initiative to test whether interventions delivered in clinical settings were effective in reducing HIV transmission risk among HIV-infected patients. Across 13 demonstration sites, patients were randomized to one of four conditions. All interventions were associated with reduced unprotected vaginal and/or anal intercourse with persons of HIV-uninfected or unknown sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 14 publications
(15 reference statements)
2
51
0
Order By: Relevance
“…Our findings suggest that the interventions provided tools for patients to feel more at ease disclosing and communicating with sex partners about sexual risk. The influence of the interventions on disclosure correspond to quantitative findings reported elsewhere (Myers et al, 2010) that these PwP interventions helped produce a shift in patients' risk towards safer sex practices.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings suggest that the interventions provided tools for patients to feel more at ease disclosing and communicating with sex partners about sexual risk. The influence of the interventions on disclosure correspond to quantitative findings reported elsewhere (Myers et al, 2010) that these PwP interventions helped produce a shift in patients' risk towards safer sex practices.…”
Section: Discussionsupporting
confidence: 82%
“…However, the high rates of disclosure and condom use observed in this analysis are consistent with other studies conducted among PLHIV who knew their HIV status and were attending clinical care. [51][52][53] All participants in this sample were PLHIV attending clinical care in a country with a …”
Section: Bachanas Et Almentioning
confidence: 99%
“…Results from the quantitative evaluation indicated that interventions delivered by either providers or specialists were effective in reducing sexual risk behavior (Myers et al, 2010). In particular, messages delivered by specialists influenced behavior change in the shorter term, while provider-delivered messages were effective and durable (Myers et al, 2010).…”
Section: University Of Miamimentioning
confidence: 98%
“…In particular, messages delivered by specialists influenced behavior change in the shorter term, while provider-delivered messages were effective and durable (Myers et al, 2010). The number of HIV infections averted depended on the type of intervention, but ranged from 2 cases averted in the assessment-only condition to 6 cases averted in the provider-delivered interventions.…”
Section: University Of Miamimentioning
confidence: 99%
See 1 more Smart Citation